Human Immunodeficiency Virus in Pregnancy a Retrospective Study on Maternal and Perinatal Outcomes - Athulya sreenivas; Anjali Suneel; Muralikrishnan Nambiar; Nikhil shetty; Anupama suresh Y (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objective: To assess the maternal and perinatal outcome in pregnant women with HIV infection and the role of Antiretroviral therapy in reducing complications of pregnancy. Methods: A retrospective analysis was conducted on data from HIV-positive mothers receiving antenatal care at a tertiary care center between February 2015 and January 2020. The study examined various adverse pregnancy outcomes in relation to antiretroviral treatment. Statistical analysis employed chi-square and Fisher’s exact tests to determine differences in distribution proportions of patients on ART versus those not on ART across various antenatal and neonatal complications, with significance attributed to p-values <0.05. Results: A total of 155 patients were found to be HIV positive. Out of this 58 were diagnosed before pregnancy and 97 during pregnancy. Miscarriage was seen in one (0.6%) patient on ART and two (1.2%) not on treatment (p-value 0.6). Sixteen (10.3%) patients underwent medical termination of pregnancy (MTP); all were given HIV-positive status and they were all on ART (p-value <0.001). Anemia was seen in eighteen (11.6%) patients out of which 14(9%) were on ART (p-value 0.01). One (0.64%) woman had thrombocytopenia and she was on ART (p-value 1). Two (1.2%) patients on ART had diabetes mellitus (p-value 0.4). One (0.64%) patient who was on ART developed polyhydramnios (p-value 1). A total of 8 (5.16%) women had hypertensive disorders; out of which 4(2.58%) were on ART (p-value 1). 11(7.09%) patients who were on ART and 6(3.8%) not on ART had preterm labor (p-value 0.2). 12(7.74%) patients who were not on ART had intrauterine growth restriction (IUGR) and 2(1.29%) on ART had IUGR. A total of 6(3.87%) patients had Intrauterine fetal demise (IUFD), of which 3(1.93%) were on ART and 3(1.93%) were not (p-value 1). Pre-labour rupture of membranes (PROM) was observed in 2(1.29%) women on ART and 11(7.09%) patients not on ART (p-value 0.004). All women (100%) had CD4 counts more than 500. All (100%) babies delivered at our center received antiretroviral therapy either with oral Nevirepine. Almost half the women (51.6%) had vaginal delivery. Almost one-fourth, 41(26.4%) had a cesarean section. All caesareans were done given obstetric indications. There were no instrumental deliveries. Our study had a total of 122 live births. All 122(100%) babies were exclusively breastfed. None of the babies delivered in our center developed HIV on follow up which was done at 6 weeks and 6 months. Nine (5.8%) patients had infections. None of these women were on ART(p-value < 0.001). Conclusion: HIV infection during pregnancy is associated with various adverse outcomes, but ART plays a crucial role in mitigating these risks and preventing mother-to-child HIV transmission. Initiating ART in all HIV-positive mothers and their infants is essential regardless of HIV status. Keywords: anemia, ART, HIV, MTP, Perinatal outcome, PROM.